Selective laser reaction synthesis of SiC, Si3N4 and HfC/SiC composites for additive manufacturing. Issue 4 (April 2023) - Peters, Adam B.; Zhang, Dajie; Hernandez, Alberto; Wang, Chuhong; Nagle, Dennis C.; Mueller, Tim; Spicer, James B.
Abstract: Selective laser reaction sintering techniques (SLRS) techniques were investigated for the production of near net-shape non-oxide ceramics including SiC, Si3 N4, and HfC/SiC composites that might be compatible with prevailing powder bed fusion additive manufacturing processes. Reaction bonded layers of covalent ceramics were produced using in-situ reactions that occur during selective laser processing and layer formation. During SLRS, precursor materials composed of metal and/or metal oxide powders were fashioned into powder beds for conversion to non-oxide ceramic layers. Laser-processing was used to initiate simultaneous chemical conversion and local interparticle bonding of precursor particles in 100 vol% CH4 or NH3 gases. Several factors related to the reaction synthesis process—precursor chemistry, gas-solid and gas-liquid synthesis mechanisms, precursor vapor pressures—were investigated in relation to resulting microstructures and non-oxide yields. Results indicated that the volumetric changes which occurred during in-situ conversion of single component precursors negatively impacted the surface layer microstructure. To circumvent the internal stresses and cracking that accompanied the conversion of Si or Hf (that expands upon conversion) or SiOx (that contracts during conversion), optimized ratios of the precursor constituents were used to produce near isovolumetric conversion to the product phase. Phase characterization indicated that precipitation of SiC from the Si/SiO2 melt formed continuous, crack-free, and dense layers of 93.7 wt% SiC that were approximately 35 µm thick, while sintered HfC/SiC composites (84.2 wt% yield) were produced from the laser-processing of Hf/SiO2 in CH4 . By contrast, the SLRS of Si/SiOx precursor materials used to produce Si3 N4 resulted in whisker formation and materials vaporization due to the high temperatures required for conversion. The results demonstrate that under appropriate processing conditions and precursor selection, the formation of near net-shape SiC and SiC composites might be achieved through single-step AM-compatible techniques. Graphical Abstract: ga1